Symptomatic treatment in facioscapulohumeral dystrophy (FSHD): a case study - Bitner-Bieleszuk, Magdalena (Medycyna Paliatywna/Palliative Medicine, 2025)
Facioscapulohumeral dystrophy (FSHD) represents the third most prevalent form of muscular dystrophy observed in the adult population, exhibiting an overall incidence of over 1 in 10,000 individuals. Some studies suggest that up to 88.6% of patients with FSHD report pain. The most common sites of pain are the lumbosacral region, lower limbs, shoulders, and neck. The article aimed to present symptoms, diagnosis, and treatment options for FSHD based on latest publications, and a case study of a patient diagnosed with the disease admitted to the Pain Management and Palliative Care Center, University Hospital, Wroclaw. Based on described case study, it can be assumed that pain management requires multidisciplinary approach, combining different interventions, such as cannabis medicines, nerve blocks, and rehabilitation. However, further studies should be conducted among patients diagnosed with dystrophy, and guidelines need to be established.